Topographies et scénographies de l’étrangeté et de l’hospitalité dans le théâtre et le cinéma grecs au tournant du xxe siècle - Georges P. Pefanis (Cahiers Balkaniques)
Jacques Derrida notes that “there can be no culture or social bond without a principle of hospitality”. But in the very definition of hospitality, strangeness is always a fundamental condition. There is no hospitality unless a stranger knocks on our door and asks to enter our home, whether immigrant or refugee – in any case: someone other than ourselves. But who is the stranger, and from whom? How the “becoming a stranger” is activated, through me or through the way I am seen by others? At this crossroads of the self as other (as Paul Ricœur would say) and the other as self, everything depends on where we place the rule of (national, religious, social, cultural) normality, in our own world or in the world of the other. The boundary that unites and separates the two worlds is the regime of hospitality.